2019
DOI: 10.9734/ajee/2019/v9i430104
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Education, Alternative Livelihood and Habitat Restoration: The Best Strategies for Conservation of Magombera Forest Reserve

Abstract: The Magombera forest is a home of endemic and endangered biological species such as Udzungwa red colobus monkey (Procolobus gordonorum) and the Magombera chameleon (Kinyongia magomberae). However, the forest is facing high threat of disappearing through resources extraction pressure from adjacent local communities. The project aimed at improving conservation of Magombera forest by involving the adjacent communities through provision of conservation education, restoration initiatives and bee keeping as alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…According to Roe et al (2015), this strategy of offering alternative livelihood options or sources of income should involve significant sensitization to avoid being misunderstood by the target community for compensation and possibly being deemed insufficient or poorly managed. This study agrees with the findings of Mahulu et al, (2019) that, in order to mitigate humanbiodiversity loss, a sustainable use method that benefits local communities while conserving natural resources is required. The study also supports the findings of Kakuba and Kanyamurwa, (2021); and Meng et al, (2020) that involving the public (Community-based biodiversity conservation approach) in wetlands management may be the best option because people will have a sense of ownership and will be willing to protect biodiversity and provide information about encroachers and other threats to biodiversity.…”
Section: Relevancy Of the Alternative Livelihood Optionssupporting
confidence: 91%
See 1 more Smart Citation
“…According to Roe et al (2015), this strategy of offering alternative livelihood options or sources of income should involve significant sensitization to avoid being misunderstood by the target community for compensation and possibly being deemed insufficient or poorly managed. This study agrees with the findings of Mahulu et al, (2019) that, in order to mitigate humanbiodiversity loss, a sustainable use method that benefits local communities while conserving natural resources is required. The study also supports the findings of Kakuba and Kanyamurwa, (2021); and Meng et al, (2020) that involving the public (Community-based biodiversity conservation approach) in wetlands management may be the best option because people will have a sense of ownership and will be willing to protect biodiversity and provide information about encroachers and other threats to biodiversity.…”
Section: Relevancy Of the Alternative Livelihood Optionssupporting
confidence: 91%
“…These strategies could take three forms, first, offering an alternative resource to the one being exploited, like in the case of encouraging locals to raise cane rats for food instead of going on a bush meat hunt (Vliet, 2011). Secondly, concentrating on initiatives that could offer an alternate job or source of income, such as beekeeping and craftmaking as alternatives to growing subsistence agriculture surrounding protected areas (Mahulu et al, 2019).Thirdly, promoting a less harmful alternative to the original technique of resource use, lessen the demand for firewood, one example of such initiatives could be the promotion of fuelefficient stoves. The three methods clearly demonstrate that initiatives to promote alternative livelihoods may occasionally succeed as stand-alone initiatives or as a part of a larger, more comprehensive integrated conservation and development program.…”
Section: Introductionmentioning
confidence: 99%
“…Training has been reported to increase local community awareness and participation in afforestation and conservation efforts 26 . Furthermore, a study from Tanzania's Magombera forest reserve found that alternative livelihood and conservation education motivated local communities to participate in forest restoration and conservation 10 . Other Tanzanian studies have found similar effects of conservation education and awareness on biodiversity conservation 9 , 27 .…”
Section: Discussionmentioning
confidence: 99%